Antibacterial, Antifungal and Phytochemical Properties of Alcea rosea Leaves Extract and Evaluate its Contribution to Healing Wound that Infected by Staphylococcus aureus - Abbas, Zainab Abdul Kareem; Mathkoor, Maryam Mansoor; Oudah, Noor Abdulameer; Ali, Firas A (Technium BioChemMed, 2024)
Medicinal plants have been used to treat various infectious illnesses in humans, a significant component of traditional medicine. Medicinal plants are currently considered a promising alternative in treating diseases caused by antibiotic-resistant microorganisms, one of the most essential therapeutic problems. Alcea rosea is a medicinal plant used for multiple therapeutic properties. This study investigated the antibacterial, antifungal, antioxidant and phytochemical properties of A. rosea aqueous extract leaves. It evaluated its contribution to healing wounds Infected by Staphylococcus aureus to verify its ability to heal wounds scientifically. Aqueous extracts of the A. rosea leaves were tested using a rat dermal excision wound model. The antibacterial activity was assessed using the broth dilution test; the antioxidant activity was evaluated using the total antioxidant capacity, phenolic and flavonoid content, ferric reducing power, and DPPH free radical scavenging. Topical use of extract creams demonstrated significant wound healing. On the 10th day, the groups treated with conventional medication and blank cream, 10% stem bark and leaf creams, and 95.8%, 96.3%, and 73.9% total wound surface closure were noted, respectively. Significant collagen formation, sparse infiltrations of inflammatory cells and re-epithelialization were observed histopathologically in the sections of healed tissue. In contrast, isolated regions of dispersed inflammatory cells and an abscess were seen in the tissues from the blank cream treatment group. S. aureus was susceptible to the antibacterial properties of the methanol stem bark extract.